Abschätzung des Restglieds im zentralen Grenzwertsatz mit der zufälligen Anzahl zufälliger Summanden - Nakas, A. (Lithuanian Mathematical Journal, 1972)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: А. Накас. Оценка остаточного члена в центральной предельной теореме со случайным числом случайных слагаемых A. Nakas. Liekamojo nario įvertinimas centrinėje ribinėje teoremoje, kai dėmenų skaičius yra atsitiktinis